Skriftkultur i ei brytingstid - Helset, Stig Jarle; Brunstad, Endre (Skriftkultur, 2019)
"The first issue of this new scientific writing series, Skriftkultur, is about current trends in writing cultural studies as a field of research and academic study. This edition focuses on the concept of 'writing culture' in a broad literacy-related context. Special attention is paid to the New Norwegian (Nynorsk) writing culture. What is meant by the concept of 'writing culture'? What are the typical traits and characteristics of writing culture today? What is the relation between writing culture and literacy? Is there a distinct New Norwegian educational tradition? And is it now time to end the relationship between New Norwegian and dialects in written language instructions? In the issue's seven original research articles, the contributors discuss different approaches to written culture and written culture studies, nationally and internationally, in both historical and contemporary contexts"